INDIVIDUALIZED LEARNING IN THE CONTEXT OF BLENDED MODE OF THE EDUCATIONAL PROCESS IN SECONDARY SCHOOL: CHALLENGES AND EXPECTATIONS - Topuzov, Oleh; Malykhin, Oleksandr; Aristova, Nataliia; Popov, Roman; Zasyekina, Tetyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Modern learning is the ultimate collaboration between teacher and student. Much like a doctor, the teacher must assess each individual’s needs, then prescribe the right solution for that person by crafting an appropriate curriculum and delivering it in a way that is meaningful. The principal aim of the research is to get an insight into contemporary issues of the individualized learning against the backdrop of blended learning in secondary school, to say nothing of the future directions for its progress and exercising. The group of researchers prepared a web-based experimental questionnaire (intended for schoolteachers and parents) targeted at illustrating the didactic potential and educational opportunities of the individualized learning as an effective remedy of preventing malign influence and retaining the quality while rendering the learning services faced with unanticipated shift to distance learning due to the COVID-19 pandemic. The inquiry-based pattern which was chosen with the aid of a voluntary response sampling technique comprised some 500 schoolteachers and parents from a various metropolitan secondary schools. Qualitative data analysis of the data obtained offer the opportunities for forming didactic rationale of the individualized learning, which could facilitate the learning process in secondary school as close as accomplishable to practical application of the learner-centered principle within a competency-based approach and digitalization of education. Alternatively, the obtained findings and logical conclusions showed the trends of teaching modes, methods and tools transformation of the individualized learning within the conditions of blended learning in secondary school.